Research on the Influencing Factors of Student Satisfaction in Labor Education in Hebei Province —Variable Selection and GLM Regression Analysis based on the Lasso Model - Hu, Siyu; Lv, Yahui (Journal of Educational Research and Policies, 2024)
Objective: With the improvement of national attention to labor education, and a more comprehensive understanding of the impact of various factors on student satisfaction, this paper investigates the universities currently implementing labor education in Hebei Province, establishes the index, and selects the main influence index based on the Lasso model. Methods: The GLM model conforming to Gaussian distribution is used to conduct regression analysis of the main influence indicators, comprehensively explore the effect of each main index on student satisfaction, and actively respond to the requirements of the country, society and individual for labor education in colleges and universities in the new era. Conclusions: The regression results show that the effects of student demand, talent training objectives, labor education organization, labor education practice implementation and labor education management supervision have a significant positive influence on student satisfaction.